The Antibiofilm Activity of Jatropha curcas L.Latex on Staphylococcus aureus ATCC 25923 - Rosmalinda Utami; Siti Rahmatul Aini; Dyke Gita Wirasisya (Natural B, Journal of Health and Environmental Sciences, 2019)
Nosocomial infections worldwide shows high rates. One of the causes of nosocomial infections is Staphylococcus aureus. S. aureus as an infectious pathogen is known to form biofilms that often cause failure of antibiotic therapy. Jatropha is one of the plants used by the community in treating various diseases, including infections. The purpose of this study was to determine the jatropha latex antibiofilm activity on S. aureus by microdilution method with crystal violet staining. The results showed that jatropha latex extract had antibiofilm activity, with biofilm inhibition percentages of 150% at concentrations of 0.625 mg/mL, while percent degradation was 189% at concentrations of 5 mg/mL. Jatropha latex extract had biofilm inhibition activity at extract concentrations of 0.625 mg/mL and biofilm degradation at extract concentration of 5 mg/mL. The result of this study can be used as topical drugs for infectious wounds.